THE OPEN-ENDED APPROACH WITH EFFECTIVE QUESTIONS STRATEGY: CAN IT ENHANCE STUDENTS’ MATHEMATICAL CREATIVE THINKING SKILLS? - Agustianingsih, Ramayanti; Putri Sasalia (Afore : Jurnal Pendidikan Matematika, 2025)
This study aims to describe the improvement of mathematical creative thinking ability of seventh grade students through the application of an Open-Ended approach integrated with the Effective Questions strategy. The study focuses on four key indicators of creative thinking: fluency, flexibility, originality, and elaboration. A quasi-experimental method was employed in this research, using a pretest-posttest group design. A purposive sampling technique was used to select one experimental class and one control class. Data were obtained through creative thinking ability test and interviews which were then analyzed descriptively and statistically. Statistical analysis was performed through a one sample t-test and N-gain. The findings indicate that integration the Open-Ended approach with effective questions strategy significantly improves students’ creative mathematical thinking, with details that (1) fluency and elaboration indicators increased in the high category (0.91 and 0.81), and (2) flexibility and originality indicators increased in the moderate category (0.61 and 0.38).